Multifrequency Dynamics of Cortical Neuromagnetic Activity Underlying Seizure Termination in Absence Epilepsy - Sun, Jintao; Gao, Yuan; Miao, Ailiang; Yu, Chuanyong; Tang, Lu; Huang, Shuyang; Wu, Caiyun; Shi, Qi; Zhang, Tingting; Li, Yihan; Sun, Yulei; Wang, Xiaoshan (Frontiers in Human Neuroscience, 2020)
Purpose: This study aimed to investigate the spectral and spatial signatures of neuromagnetic activity underlying the termination of absence seizures. Methods: Magnetoencephalography (MEG) data were recorded from 18 drug-naive patients with childhood absence epilepsy (CAE). Accumulated source imaging (ASI) was used to analyze MEG data at the source level in seven frequency ranges: delta (1-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (12-30 Hz), gamma (30-80 Hz), ripple (80-250 Hz), and fast ripple (250-500 Hz). Result: In the 1-4, 4-8 and 8-12 Hz ranges, the magnetic source during seizure termination appeared to be consistent over the ictal period and was mainly localized in the frontal cortex (FC) and parieto-occipito-temporal junction (POT). In the 12-30 and 30-80 Hz ranges, a significant reduction in source activity was observed in the frontal lobe during seizure termination as well as a decrease in peak source strength. The ictal peak source strength in the 1-4 Hz range was negatively correlated with the ictal duration of the seizure, whereas in the 30-80 Hz range, it was positively correlated with the course of epilepsy. Conclusion: The termination of absence seizures is associated with a dynamic neuromagnetic process. Frequency-dependent changes in the FC were observed during seizure termination, which may be involved in the process of neural network interaction. Neuromagnetic activity in different frequency bands may play different roles in the pathophysiological mechanism during absence seizures.